Analisa Sikap Dan Kepuasan Konsumen Dalam Pemasaran Produk - Retno Syafitri (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2020)
Lifestyle in society in a region or country that differentiates consumer attitudes and follows current trends. Understanding Consumer Attitudes or Consumer Behavior is an important task for marketers. Marketers must understand consumer purchasing behavior that follows trends from time to time which continues to change according to the times. The goal in this article is to increase knowledge about consumer attitudes and satisfaction in product marketing. using theoretical research research methods obtained from books, articles, and websites. the product becomes the reason for consumers in determining their attitudes and satisfaction.